Relevant Developments in the Use of Three‐Component Reactions for the Total Synthesis of Natural Products. The last 15 Years - Larghi, Enrique Leandro (2024)
Multicomponent reactions (MCRs) are a valuable strategy toward complex polysubstituted compounds because they simplify long sequences, increasing their efficiency. The total synthesis of natural products achieved since 2004 through the use of three-component reactions as a strategic MCR approach is reviewed. Successful sequences are described, along with relevant information on the isolation and bioactivity of the selected targets.